2022
DOI: 10.1161/circulationaha.121.058411
|View full text |Cite|
|
Sign up to set email alerts
|

Proteasomal Degradation of TRAF2 Mediates Mitochondrial Dysfunction in Doxorubicin-Cardiomyopathy

Abstract: Background: Cytokines such as tumor necrosis factor-α (TNFα) have been implicated in cardiac dysfunction and toxicity associated with doxorubicin (DOX). Although TNFα can elicit different cellular responses, including survival or death, the mechanisms underlying these divergent outcomes in the heart remain cryptic. The E3 ubiquitin ligase TRAF2 (TNF receptor associated factor 2) provides a critical signaling platform for K63-linked polyubiquitination of RIPK1 (receptor interacting protein 1), cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In addition, FHL2 + Cardiomyocytes scored higher on death, indicating more severe damage (Figure 2E and 2F) [13] . During the fibrinolytic phase of CAC, the PI3K-AKT pathway is activated in both these cardiomyocyte subsets, which further promotes the formation of PIP1-TRAF2 death corpuscles and exacerbates cardiomyocyte death (Figure 2D) [14] .…”
Section: Results 2: Cardiac Intercellular Developmental Transition In...mentioning
confidence: 99%
“…In addition, FHL2 + Cardiomyocytes scored higher on death, indicating more severe damage (Figure 2E and 2F) [13] . During the fibrinolytic phase of CAC, the PI3K-AKT pathway is activated in both these cardiomyocyte subsets, which further promotes the formation of PIP1-TRAF2 death corpuscles and exacerbates cardiomyocyte death (Figure 2D) [14] .…”
Section: Results 2: Cardiac Intercellular Developmental Transition In...mentioning
confidence: 99%
“…Conversely, gain of function of TRAF2 suppressed the cardiotoxic effects of doxorubicin in vitro and in vivo. 1 Nevertheless, the net effect of TRAF2 on the antineoplastic properties of doxorubicin was not investigated in this study and warrants future investigation in tumor-bearing mouse models. Optimal therapies for doxorubicin cardiotoxicity either would not affect or would enhance doxorubicin antineoplastic efficacy.…”
Section: In Responsementioning
confidence: 93%
“…We thank Drs Shi et al for their interest in our article. 1 We appreciate their comments and discussion.…”
Section: In Responsementioning
confidence: 94%
“…We read with interest the article by Dhingra et al 1 who demonstrated that the cardiotoxic properties of doxorubicin (Dox) are mediated by proteasomal degradation of the innate immune adapter protein TRAF2 (tumor necrosis factor receptor associated factor 2). This study provides an interesting observation that restoration of TRAF2 in vitro and in vivo suppressed Dox-induced mitochondrial injury and necrotic cell death and rescued cardiac function.…”
Section: To the Editormentioning
confidence: 99%